Functional Multipotency of Stem Cells: What Do We Need from Them in the Heart? - Pablo Díez Villanueva; Ricardo Sanz-Ruiz; Alberto Núñez García; María Eugenia Fernández Santos; Pedro L. Sánchez; Francisco Fernández-Avilés (Stem Cells International)
After more than ten years of human research in the field of cardiac regenerative medicine, application of stem cells in different phases of ischemic heart disease has come to age. Randomized clinical trials have demonstrated that stem cell therapy can improve cardiac recovery after the acute phase of myocardial ischemia and in patients with chronic ischemic heart disease, and several efficacy phase III trials with clinical endpoints are on their way. Nevertheless, a complete knowledge on the mechanisms of action of stem cells still remains elusive. Of the three main mechanisms by which stem cells could exert their benefit, paracrine signaling from the administered cells and stimulation of endogenous repair are nowadays the most plausible ones. However, in this review we will define and discuss the concept of stem cell potency and differentiation, will examine the evidence available, and will depict future directions of research.